La oposición y los recursos en la jurisdicción voluntaria - Alonso Furelos, Juan Manuel (Revista de Derecho de la UNED (RDUNED), 2015)
Abordo en estas líneas la oposición al Acto de jurisdicción voluntaria solicitado y la ulterior oposición al contenido del Auto que sobre él se pronuncia y el recurso de apelación contra el mismo. Todas son manifestaciones impugnativas, con un régimen jurídico diferenciado, a través del proceso o del recurso. Lo hacemos examinando su evolución histórica, el régimen jurídico del momento presente y con una somera referencia al Anteproyecto de Ley de Jurisdicción Voluntaria. Terminaremos con unas breves conclusiones. I approach in these lines the opposition to the Act of voluntary jurisdiction requested and the subsequent opposition to the content Auto that on him is pronounced and the resource of appeal against the same one. They all are impugning manifestations, with a juridical differentiated system, through the process or the resource. We do it examining its historical evolution, the juridical system of the present moment and with a shallow reference to the Draft Bill of Voluntary Jurisdiction. We will end with a few brief conclusions.